MARX'S CONCEPT OF MAN IN MUSLIM SCHOLARS PERSPEKTIVE - Daud, Ilyas; Munthe, Bermawy; Baidhowi, Ahmad (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2018)
This paper analyzed the human concept according to Marxism in the view of Muslim thinkers. This paper was made because of the reading of material-based Marxist concepts and out from the transcendent elements, including in view of human beings. For this reason Marxism is very necessary to be seen from the perspective of human concepts according to Muslim thinkers who are represented by groups of Muslim philosophers and groups of mufassir. The results of this result showed that the main different and criticism of Marxism is his thinking that humanity is the result of his own creation based on materials. This refers to the idea of man-centered, autonomous, physical-biological man, without sou. Human life depends on maerials,it does not depend on things which are supernatural like God so that man must be united with nature. Marx's view of man is very different from the concept of man according to Muslim thinkers. According to them, man was created by his Lord and deeply connected with God. Besides they have physical elements, humans also have elements of the soul or nafs which very dependent on God. Humans made the Khalifah to control nature as a medium of worship to God.